Outcome measures used in forensic mental health research: a structured review. - Chambers, J; Yiend, J; Barrett, B; Burns, T; Doll, H; Fazel, S; Jenkinson, C; Kaur, A; Knapp, M; Plugge, E; Sutton, L; Fitzpatrick, R (2009)
BACKGROUND: The evidence base for forensic mental health (FMH) services has been developing since the late 1990s. Are outcome measures sound enough for the evaluation tasks? AIMS: To identify, from published literature, outcome measures used in FMH research and, where feasible, assess their quality. METHOD: A structured review was undertaken of trials and intervention studies published between 1990 and 2006. Details of outcome variables and measures were abstracted. Evidence regarding most frequently occurring outcome measures was assessed. RESULTS: Four hundred and fifty different instruments were used to assess outcomes, incorporating 1038 distinct variables. Very little evidence could be found to support the measurement properties of commonly used instruments. CONCLUSIONS: and implications for practice There is little consistency in the use of outcome measure in FMH research. Effort is required to reach consensus on validated outcome measures in this field in order to better inform practice.